CAPITAL INTENSITY, LIQUIDITY, LEVERAGE TERHADAP TAX AVOIDANCE DENGAN PERTUMBUHAN PENJUALAN SEBAGAI VARIABEL MODERASI PERIODE 2012-2019 - Alvina; Ngadiman; Yustina Peniyanti Jap (Fakultas Ekonomi Universitas Tarumanagara, 2023)
Indonesia is a developing country, where one of the largest sources of income for the Indonesian state comes from its tax income. With the existence of government regulations to provide incentives to reduce tax rates on entities, there are still differences of opinion between the government, which causes corporate taxpayers to reduce tax payments illegally or legally. In this study, the method of legal tax reduction. A research was conducted on capital intensity, liquidity, and leverage on tax avoidance with sales growth as a moderating variable in mining sector companies listed on the IDX for the period 2012 - 2019. The research hypothesis is that capital intensity and leverage can have a significant and positive effect on tax avoidance, liquidity has no effect. against tax avoidance, and sales growth weakens the influence of Capital Intensity, Liquidity, and Leverage on Tax Avoidance. The sample selection method was purposive sampling and 8 companies were selected as samples. Techniques for processing data with multiple regression analysis methods with the help of SPSS and Microsoft Office 2013 programs. The results showed that capital intensity, liquidity, and leverage had no significant effect, while sales growth did not affect the relationship between capital intensity, liquidity and leverage on tax avoidance